The relationship between SARA fractions and crude oil stability - Siavash Ashoori; Mehdi Sharifi; Mohammad Masoumi; Mehdi Mohammad Salehi (Egyptian Journal of Petroleum)
Asphaltene precipitation and deposition are drastic issues in the petroleum industry. Monitoring the asphaltene stability in crude oil is still a serious problem and has been subject of many studies. To investigate crude oil stability by saturate, aromatic, resin and asphaltene (SARA) analysis seven types of crudes with different components were used. The applied methods for SARA quantification are IP-143 and ASTM D893-69 and the colloidal instability index (CII) is computed from the SARA values as well. In comparison between CII results, the values of oil compositions demonstrated that the stability of asphaltenes in crude oils is a phenomenon that is related to all these components and it cannot be associated only with one of them, individually.